Assessment of the functional impact on the pre‐mRNA splicing process of 28 nucleotide variants associated with Pompe disease in GAA exon 2 and their recovery using antisense technology. Issue 11 (29th July 2019) - Goina, Elisa; Musco, Lorena; Dardis, Andrea; Buratti, Emanuele
Abstract: Glycogen storage disease II (GSDII), also called Pompe disease, is an autosomal recessive inherited disease caused by a defect in glycogen metabolism due to the deficiency of the enzyme acid alpha‐glucosidase (GAA) responsible for its degradation. So far, more than 500 sequence variants of the GAA gene have been reported but their possible involvement on the pre‐messenger RNA splicing mechanism has not been extensively studied. In this work, we have investigated, by an in vitro functional assay, all putative splicing variants within GAA exon 2 and flanking introns. Our results show that many variants falling in the canonical splice site or the exon can induce GAA exon 2 skipping. In these cases, therefore, therapeutic strategies aimed at restoring protein folding of partially active mutated GAA proteins might not be sufficient. Regarding this issue, we have tested the effect of antisense oligonucleotides (AMOs) that were previously shown capable of rescuing splicing misregulation caused by the common c.‐32‐13T>G variant associated with the childhood/adult phenotype of GSDII. Interestingly, our results show that these AMOs are also quite effective in rescuing the splicing impairment of several exonic splicing variants, thus widening the potential use of these effectors for GSDII treatment.